Cellular immunotherapy for acute myeloid leukemia: How specific should it be?. (May 2019) - Lee, Jong Bok; Chen, Branson; Vasic, Daniel; Law, Arjun D.; Zhang, Li
Abstract: Significant improvements in the survival of patients with hematological cancers following hematopoietic stem cell transplantation provide evidence supporting the potency of immune cell-mediated anti-leukemic effects. Studies focusing on immune cell-based cancer therapies have made significant breakthroughs in the last few years. Adoptive cellular therapy (ACT), and chimeric antigen receptor (CAR) T cell therapy, in particular, has significantly increased the survival of patients with B cell acute lymphoblastic leukemia and aggressive B cell lymphoma. Despite antigen-negative relapses and severe toxicities such as cytokine release syndrome after treatment, CAR-T cell therapies have been approved by the FDA in some conditions. Although a number of studies have tried to achieve similar results for acute myeloid leukemia (AML), clinical outcomes have not been as promising. In this review, we summarize recent and ongoing studies on cellular therapies for AML patients, with a focus on antigen-specific versus -nonspecific approaches.